1981
DOI: 10.1161/01.cir.63.6.1289
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic investigation of endomyocardial biopsy samples in hypertrophy and cardiomyopathy. A semiquantitative study in 48 patients.

Abstract: SUMMARY Electron microscopic and statistical analyses of 66 right ventricular biopsies from 48 patients were undertaken to investigate whether quantitative differences exist between those patients with "ordinary" myocardial hypertrophy and those suffering from a form of cardiomyopathy.The electron microscopic changes were scored and correlated with hemodynamic variables such as ejection fraction (EF), left ventricular end-diastolic pressure (LVEDP) and length of history. The patients were followed for an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 30 publications
3
35
0
2
Order By: Relevance
“…No relationship between morphological changes and cardiac functional status has been identified (40). These studies, however, were performed before the availability of genotype analysis for FHC; thus, no information is currently available regarding allele-or gene-specific ultrastructural findings.…”
Section: Discussionmentioning
confidence: 99%
“…No relationship between morphological changes and cardiac functional status has been identified (40). These studies, however, were performed before the availability of genotype analysis for FHC; thus, no information is currently available regarding allele-or gene-specific ultrastructural findings.…”
Section: Discussionmentioning
confidence: 99%
“…5 Based on these hallmarks, the nuclei were nuclei were evaluated per specimen and the mean value of the scoring was determined as the nuclear hypertrophy score of the electron microscopic specimen. Similarly, nuclear hypertrophy was scored as 0-3 using the paraffin-sections stained with hematoxylin-eosin under light microscopy based on the degree of nuclear deformity and the thickness of the hematoxylin stain of nuclear chromatin (Fig 2A).…”
Section: Scoring Of Nuclear Hypertrophy By Electron and Light Microscopymentioning
confidence: 99%
“…The nuclear change has been well characterized as "hypertrophied nucleus" by the morphological hallmarks of severe crenation of the nuclear membrane (bizarre shape) and widespread clumping of chromatin. [3][4][5] However, the significance of such dramatic alteration of the nuclear phenotype in hypertrophic hearts is largely unknown. We previously reported that hypertrophied nuclei in the myocytes of human hearts with dilated cardiomyopathy (DCM) were accompanied by increased activity of DNA repair/synthesis.…”
mentioning
confidence: 99%
“…Much less is known about arrhythmia mechanisms in patients with IDC. There is some evidence of disturbed conduction in patients with IDC (2,(5)(6)(7)(8), and there is considerable evidence of abnormal cellular function (9-1 1 ), abnormal passive electrical properties ( 12,13), and abnormal morphologic features that could contribute to abnormal propagation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, we are not aware of any previous attempts to systematically examine the spread ofelectrical activity in cardiomyopathic states in humans or in animal models.…”
Section: Introductionmentioning
confidence: 99%